Survival and Complication Rates of Fixed Restorations Supported by Locking‐Taper Implants: A Prospective Study with 1 to 10 Years of Follow‐Up. Issue 6 (18th April 2014) - Mangano, Francesco; Macchi, Aldo; Caprioglio, Alberto; Sammons, Rachel Lilian; Piattelli, Adriano; Mangano, Carlo
Abstract Purpose The aim of this 10‐year follow‐up study was to evaluate the implant survival and complication rates of fixed restorations supported by locking‐taper implants. Materials and Methods Over a 10‐year period (January 2002 to December 2011) all patients referred to a single private practice for treatment with fixed restorations (single crowns, SCs; fixed partial prostheses, FPPs; fixed full arches, FFAs) supported by dental implants were considered for inclusion in the study. At each annual follow‐up session, clinical, radiographic, and prosthetic parameters were assessed. The surviving implant‐supported restorations were defined as "complication free" in the absence of any biological or prosthetic (mechanical or technical) complication. The cumulative implant survival and the "complication‐free" survival of fixed implant‐supported restorations were identified using the Kaplan‐Meier method. The Log‐rank test was used to identify correlations between the study variables. Results In total, 1494 locking‐taper implants (727 maxilla, 767 mandible) were placed in 642 patients (356 males, 286 females). Nineteen implants (12 maxilla, 7 mandible) failed. Implant failures were attributed to lack of osseointegration (14 implants), peri‐implantitis (4 implants), and mechanical overloading (1 implant). An overall 10‐year cumulative implant survival rate of 98.7% (98.3% maxilla, 99.1% mandible) was found. The implant survival rates did not significantly differ with respect to implant location, position, bone type, implant length and diameter, and type of restorations. Among the surviving implant‐supported restorations (478 SC, 242 FPP, 19 FFA), a few biological (11/739: 1.4%) and prosthetic (27/739: 3.6%) complications were reported. The incidence of mechanical complications was low (3/739: 0.4%), with three loosened abutments in three SCs (3/478: 0.6%), and no abutment fractures; technical complications were more frequent (24/739: 3.2%), with an incidence of decementation of 2.0% (SC 2.0%, FPP 1.6%, FFA 5.2%) and ceramic/veneer chipping/fracture of 1.2% (SC 0.0%, FPP 2.8%, FFA 10.5%). A 10‐year cumulative "complication‐free" survival of restorations of 88.6% (SC 91.7%, FPP 83.1%, FFA 73.8%) was reported. The complication rates differ significantly with respect to the type of restoration (p < 0.05). Conclusions Fixed restorations on locking‐taper implants seem to be a successful procedure for the rehabilitation of partially and completely edentulous arches.